Skeletal muscle strength improvement - Chan, Alvin Wei Sheng (2015)
Muscular imbalance has been known to cause discomfort and pain, and the most common complaints are those at the neck and back. The resulting adverse effects from a lack of proper muscle conditioning are extensive and include poor posture, reduced strength and limited flexibility. These will ultimately impede one’s ability to perform even common daily tasks, especially with increasing age, leading to a decline in quality of life. Many studies have shown that core muscle strengthening had been effective in alleviating pain in the lower back. Researches have also been conducted to address upper back and neck pain by investigating the trapezius muscle. However, no data concerning the impact of trapezius muscle conditioning on the middle-aged population was available. This project involved an experimental study titled “Trapezius Conditioning for Skeletal Muscle Stability”, whereby a series of tests and exercises was conducted on middle-aged male participants to investigate the effects of muscle conditioning of the trapezius. The results were analysed on four fronts, namely muscle endurance, muscle flexibility, upper body posture and body composition. There were positive results in the fields of muscles flexibility, upper body posture, and especially muscle endurance. With regards to body composition, however, the data collected indicated no significant changes as a result of the training regime. Concurrently, an application software named “FitRoute” was developed up to its prototype stage, in tandem with the study. FitRoute, a progress tracking software, was designed to assist users in tracking their route to fitness as well as to motivate users to maintain a healthy lifestyle. This project strived to gain additional insights to assist the middle-aged population in retaining the ability to perform daily activities with vigour and at the same time, without undue fatigue, well into their twilight years.